Salt Intakes, Knowledge, and Behavior in Samoa: Monitoring Salt‐Consumption Patterns Through the World Health Organization's Surveillance of Noncommunicable Disease Risk Factors (STEPS). Issue 9 (3rd February 2016) - Webster, Jacqui; Su'a, Sarah Asi Faletoese; Ieremia, Merina; Bompoint, Severine; Johnson, Claire; Faeamani, Gavin; Vaiaso, Miraneta; Snowdon, Wendy; Land, Mary‐Anne; Trieu, Kathy; Viali, Satu; Moodie, Marj; et al.
Abstract : This project measured population salt intake in Samoa by integrating urinary sodium analysis into the World Health Organization's (WHO's) STEPwise approach to surveillance of noncommunicable disease risk factors (STEPS). A subsample of the Samoan Ministry of Health's 2013 STEPS Survey collected 24‐hour and spot urine samples and completed questions on salt‐related behaviors. Complete urine samples were available for 293 participants. Overall, weighted mean population 24‐hour urine excretion of salt was 7.09 g (standard error 0.19) to 7.63 g (standard error 0.27) for men and 6.39 g (standard error 0.14) for women ( P =.0014). Salt intake increased with body mass index ( P =.0004), and people who added salt at the table had 1.5 g higher salt intakes than those who did not add salt ( P =.0422). A total of 70% of the population had urinary excretion values above the 5 g/d cutoff recommended by the WHO. A reduction of 30% (2 g) would reduce average population salt intake to 5 g/d, in line with WHO recommendations. While challenging, integration of salt monitoring into STEPS provides clear logistical and cost benefits and the lessons communicated here can help inform future programs.